PENGARUH PENAMBAHAN TEPUNG DAUN KEMANGI (Acimum spp) DALAM PAKAN TERHADAP PERFORMANS AYAM BROILER - Merry Simanjuntak (JURNAL HUTAN PULAU-PULAU KECIL, 2017)
The Chicken broiler is a type of superior race chicken that has high genetic properties, especially in growth. The use of herbs as medicines in medicine is now starting to increase, which is evident from the many traditional drugs manufacturers on the market. One of the herbs that can be used as an antibiotic for livestock is basil (Ocimum sp). Basil contains beta-carotene (provitamin A), which supports the function of vision, improves antibody function (influences immune function), protein synthesis to support growth process and as the antioxidant (Adnyana and Firmansyah, 2006). The purpose of this study was to determine the effect of the addition of basil leaves flour up to 12% level against broiler performance. The experiment was carried out experimentally using a completely randomized design (CRD). The results of statistical analysis showed that the addition of basil meal powder into the feed did not affect to feed consumption between levels (P> 0). The result of the statistical analysis showed that the addition of basil meal powder into the feed had no effect (P> 0,05) to the increase in body weight. The result of the statistical analysis showed that the treatment with the addition of basil powder into the feed had no effect (P> 0,05) to feed conversion. The result of this research can be concluded that the addition of basil powder into feed up to 12% level did not give significantly different effect on production performance such as feed consumption, body weight gain and feed conversion of the broiler.